1. ## Function Notation

a bit stuck here...

question:

compute $\frac{4g(-5)+[g(2)]^{2}}{-2g(3)}$

also:
how would i solve f[k(-8)] , when i am given other variables for f and k to solve for other functions? i may need to explain that question better, but need to get away from the computer quick

explanation of how to solve it would be great.... not looking for the answer.

2. Originally Posted by pychon
a bit stuck here...

question:

compute $\frac{4g(-5)+[g(2)]^{2}}{-2g(3)}$

would help to know how g(x) is defined ...

also:
how would i solve f[k(-8)] , when i am given other variables for f and k to solve for other functions? i may need to explain that question better, but need to get away from the computer quick

ditto ... f(x) = ??? and k(x) = ???
...

3. first questions variables:
Code:
x| -5 |-4|-3|-2|-1| 0|  1| 2| 3
---------------------------------
y| 12 | 9| 4| 0|-1|-3| -5|-6|-8
i suspect i should take and write as
$\frac{4g(-5)+[g(2)]^{2}}{-2g(3)}$

$\frac{4(-3)(-5)+[-6(2)]^{2}}{-2(0)(3)}$

second question variables are:

$f(x) = -4x+3$

$k(x) = \sqrt[3]{x}$

so, $f[k(-8)]$ would be $f(x) = -4(-8)+3$ or is it $-4(\sqrt[3]{2})+3$

my college math book doesn't explain a bleeping thing how to do what. so if anyone knows of any literature, or preferably videos, on explicit functions and relationship problems wth problems like these that would be great... even domain and range.

4. Originally Posted by skeeter

actually, was just watching those... but doesn't explain similar problems i have posted (yet) and his domain and range -infinity?!- come on use math terminology... $x \leq n$ or $x \geq n$

5. first questions variables:
Code:
x| -5 |-4|-3|-2|-1| 0|  1| 2| 3
---------------------------------
y| 12 | 9| 4| 0|-1|-3| -5|-6|-8
if the table represents g(x) , then g(-5) = 12 , g(2) = -6 , and g(3) = -8

$\displaystyle \frac{4g(-5)+[g(2)]^{2}}{-2g(3)}$

should be

$\displaystyle \frac{4(12)+(-6)^{2}}{-2(-8)} = \frac{48 + 36}{16}$

second question variables are:

$f(x) = -4x+3$

$k(x) = \sqrt[3]{x}$

$f[k(-8)] = f[\sqrt[3]{-8}] = f(-2) = -4(-2) + 3 = 11$